AN ANALYSIS OF GEOLOGICAL TEXTBOOKS, AT 1830-1930 - Makri K., K.; Pavlides, S.B.; Kastanis, N. (Bulletin of the Geological Society of Greece, 2010)
The geological education in Greece is essentially rooted in the second half of the 19th century. Since 1836, when the Secondary Education was legislated in Greece, in spite of the fact that Geology is referred to all educational programs, geology was not taught before 1880, due to the lack of competent teachers and their books. The deficiency is limited with the first complete edition of the book Geology addressed in Secondary Education. This work presents and analyzes the content of a representative sample of school textbooks of Geology, as the approach of geological theories, including the definition and interpretation of geological phenomena, is the result of the trend, followed by each author.